Acquisition of a Stable and Transferable blaNDM-5-Positive Plasmid With Low Fitness Cost Leading to Ceftazidime/Avibactam Resistance in KPC-2-Producing Klebsiella pneumoniae During Treatment - Huang, Jiangqing; Zhang, Shengcen; Zhao, Zhichang; Chen, Min; Cao, Yingping; Li, Bin (Frontiers in Cellular and Infection Microbiology, 2021)
The emergence and prevalence of carbapenem-resistant Enterobacteriaceae (CRE) have drawn worldwide attention. Ceftazidime/avibactam (CAZ/AVI) gives us a valuable alternative strategy to treat CRE infections. Unfortunately, CAZ/AVI resistance could occur during CAZ/AVI treatment. The CAZ/AVI-resistant Carbapenem-resistant Klebsiella pneumoniae (CR-KP) (KP137060) and earlier CAZ/AVI-susceptible isolate (KP135194) from the same hospitalized patient were collected at Fujian Medical University Union Hospital between October and November 2019. In this study, CAZ/AVI MICs of CAZ/AVI-susceptible and -resistant isolates (KP135194 and KP137060) were 4 mg/L and 128 mg/L, respectively; and the two isolates had the same antibiotic resistance pattern to other carbapenems. Two strains were then submitted for whole-genome sequencing and bioinformatic analysis. ompK36 was not detected in two isolates. No mutation was observed in blaKPC-2, ompK35 and ompK37 in this study and there was no significant difference of the expression in blaKPC-2, ompK35 and ompK37 between the two isolates (p>0.05). Two isolates were sequence type 11 and harbored blaKPC-2, blaSHV-182 and blaTEM-1B. Compared with KP135194, KP137060 harbored an additional blaNDM-5 positive plasmid. blaNDM-5 gene could be successfully transferred into E. coli J53 at a conjugation frequency of 1.14×10-4. Plasmid stability testing showed that blaKPC-2- and blaNDM-5-harboring plasmids were still stably maintained in the hosts. Growth assay and growth competition experiments showed there was no significant difference in fitness cost between two CR-KP isolates. Our study described the acquisition of a blaNDM-5-harboring plasmid leading to resistance to ceftazidime/avibactam in KPC-2-producing Klebsiella pneumoniae during treatment. This phenomenon deserves further exploration.